Elastic and electrical properties of calcite-cemented artificial sandstones based on a new manufacturing method - Wang, Pan; Han, Tongcheng; Fu, Li-Yun (Frontiers in Earth Science, 2023)
Calcite cement is widely existing in sandstones and can significantly affect the elastic and electrical properties of sandstones. Accordingly, understanding the effects of calcite cement on the elastic and electrical rock properties is of key importance for the accurate characterization of sandstone reservoirs through seismic and electromagnetic surveys. To obtain such knowledge, we design and implement dedicated laboratory experiments to investigate the effects of calcite cement and porosity on the P- and S-wave velocities and electrical resistivity of synthetic calcite-cemented sandstones made using a new recipe. The experimental results show that elastic velocities and electrical resistivity generally decrease with increasing porosity when the content of the calcite cement keeps constant, whereas the elastic and electrical rock properties exhibit complex variation with cement content in sandstones with approximately the same porosity. Analyses and interpretation of the experimental data indicate that the elastic and electrical rock properties are affected jointly by porosity, the content and distribution of the calcite cement, as well as the microstructure of the pore space resulting from the different axial stress employed for the consolidation of the rock samples. The results have revealed the mechanisms of how porosity and calcite cement affect the elastic and electrical properties of calcite-cemented sandstones, and provided a theoretical basis for the accurate characterization of sandstone reservoirs through seismic and electromagnetic surveys.